Randomized double-blind trial to evaluate the effectiveness of topical administration of propylene glycol in arsenical palmar keratosis - Dina, Ashrafun Naher; Misbahuddin, Mir (Bangladesh Journal of Pharmacology, 2011)
Keratosis, one of the earliest skin manifestations of arsenicosis, can be treated by either oral or topical formulation of drug. In this study we examined the effectiveness and tolerance of propylene glycol for the treatment of arsenical palmar keratosis. Sixty patients of arsenicosis with palmer keratoses were randomly divided into three groups and different concentrations (15, 30 and 45%) of propylene glycol were applied topically into their palms once at bedtime for eight weeks. The perception of the patient about the progress of treatment was scored with 'Likert scale'. The mean (±SD) score of patient's perception following completion of treatment were 1.27 ± 1.26 (using 15% propylene glycol), 2.88 ± 1.26 (30% propylene glycol), and 3.75 ± 1.06 (45% propylene glycol) respectively. The scores increased with higher concentrations. Thirty percent or more concentration of propylene glycol was effective for mild to severe form of keratosis. Propylene glycol was well tolerable. In conclusion, both roughness and thickness of arsenical palmar keratosis can be reduced using propylene glycol and as the concentration of the drug increases it increases its effectiveness without any significant adverse effect.